2009
DOI: 10.1152/ajpgi.90730.2008
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cells in fetal intestine produce chemerin to recruit macrophages

Abstract: Macrophages are first seen in the fetal intestine at 11-12 wk and rapidly increase in number during the 12- to 22-wk period of gestation. The development of macrophage populations in the fetal intestine precedes the appearance of lymphocytes and neutrophils and does not require the presence of dietary or microbial antigens. In this study, we investigated the role of chemerin, a recently discovered, relatively selective chemoattractant for macrophages, in the recruitment of macrophage precursors to the fetal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 64 publications
1
50
0
Order By: Relevance
“…Adiponectin and chemerin are released from adipocytes, but whereas adiponectin is preferentially produced by these cells, chemerin is also synthesized by other cells like fetal intestinal epithelial cells or hepatocytes [26,27]. Comparison of different fat depots revealed that visceral fat produces higher amounts of adiponectin compared to subcutaneous adipose tissue [28].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin and chemerin are released from adipocytes, but whereas adiponectin is preferentially produced by these cells, chemerin is also synthesized by other cells like fetal intestinal epithelial cells or hepatocytes [26,27]. Comparison of different fat depots revealed that visceral fat produces higher amounts of adiponectin compared to subcutaneous adipose tissue [28].…”
Section: Discussionmentioning
confidence: 99%
“…Based on reports of Chemerin signaling in intestinal epithelial cell differentiation (Maheshwari et al, 2009), we hypothesized that Chemerin/ChemR23 signaling might also mediate DE-DM signaling in tooth development. The findings presented here lead to the novel hypothesis that Chemerin/ChemR23 signaling may facilitate proper DE-DM cell interactions during tooth development.…”
Section: Introductionmentioning
confidence: 99%
“…Chemerin, the endogenous ligand of ChemR23, is a newly discovered adipokine that regulates adipocyte differentiation and modulates chemotaxis and recruitment of NK cells, dendritic cells, and macrophages [8][9][10] . Chemerin is strongly associated with markers of inflammation, metabolic syndrome components, and atherosclerosis [11] , for which endothelial dysfunction is a fundamental etiological factor.…”
Section: Introductionmentioning
confidence: 99%